Um caminho para inovação no Tocantins: proposta do novo marco legal de ciência, tecnologia e inovação - Marinho, Siméia Carvalho de Oliveira (Universidade Federal do Tocantins, 2022)
This dissertation aims to present the results of a research developed in order to learn the legal scenario of innovation in Tocantins. The research key problem was to identify a way for the state of Tocantins to legally articulate and organize its innovation system (IS). The assumption outlined was that the innovation policy (IP) would be the best way to organize, structure and institute a new scenario for the IS in Tocantins. This study applied the deductive method, with the applied purpose of building products for the outlined problem. To achieve the objectives proposed in the research project, the exploratory and descriptive formats were followed, with two main procedural instruments: the bibliographic and the documentary. In the data analysis, a qualitative approach was used. The research results enabled the construction of the state's innovation trajectory and demonstrated some impediments to instituting an IP in the current scenario of Science, Technology and Innovation (ST&I) in Tocantins. The IS of Tocantins went through several periods of destructuring, taking the opposite direction to what has been designed at the national level. Tocantins has made very little progress, both in regimental and institutional scope and, its state legislation is outdated in relation to the national ST&I legislation framework. Given this state scenario, a New Legal Framework of Science, Technology and Innovation is suggested for the state of Tocantins and the public consultation project that will subsidize the legislature. The New Legal Framework project, in progress in the Legislative Assembly of Tocantins, through state deputy teacher Júnior Geo, is a set of updates to the state legislative framework on ST&I: a) Amendment to the Constitution of the State of Tocantins, b) revocation of Innovation Law No. 2,458 of 07/05/2011 and c) update of State Complementary Law No. 71, of 03/31/2011 and of Law No. 3,421, of 03/08/2019. It is considered that the proposal of the New Legal Framework could be an instrument to assist the state in the organization of its IS to advance in the promotion of research, science, technology, entrepreneurship and innovation with a focus on progress and regional development.